Pengaruh Legitimacy Power Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dimediasi oleh Trust in Authority - Marcella; Wahyu Prasetya (Syntax Idea)
This study aims to examine the impact of legitimacy power on the compliance of individual taxpayers, with trust in authority as a mediating factor. Employing quantitative research methods, the study involved 144 participants. Data collection was conducted through the distribution of questionnaires using Google Form. The analysis was carried out using Partial Least Square (PLS) via the SmartPLS 4 software. The findings of the study indicate that (1) legitimacy power significantly influences trust in authority; (2) legitimacy power significantly affects the compliance of individual taxpayers; (3) trust in authority does not significantly impact the compliance of individual taxpayers; and (4) trust in authority does not serve as a mediator in the relationship between legitimacy power and individual taxpayer compliance.Keywords: Legitimacy power, Trust In Authority, Taxpayer’s Compliance, Mediation, SmartPLS.